ATMEGA328P-Based Hand Sanitizer Pump to Prevent The Transmission of The Covid-19: Pompa Hand Sanitizer Tanpa Sentuh Berbasis ATMEGA328P dalam Upaya Mencegah Penularan Virus Covid-19 - Asma Ainuddin; Tino Suhaebri (Unit Penelitian dan Pengabdian Kepada Masyarakat, AK-Manufaktur Bantaeng, 2023)
The covid19 virus requires the application of strict health protocols. Among them avoid direct contact with surrounding objects or other people. Apart from using masks, hand washing, the use of hand sanitizers is also recommended. The use of conventional hand sanitizers is generally less effective when used by many people. Therefore, there is high recommendation for using a non-touch tool especially for people while using a public hand sanitizer bottle pump. The automatic hand sanitizer pump based on a microcontroller is one of the solutions. In the manufacture process of an automatic hand sanitizer pump, the method applied is to create a design concept, manufacture a case, electrical circuit, and assembling the whole product. From the process of making the product, it produces several types of tests, namely distance and voltage sensors, the reliability of hand sanitizer pumps, battery charging time, and the number of pumps process until the hand sanitizer runs out. The testing results showing that the pump will activate when an object or hand is detected at a distance of ≤ 10 cm from the sensor, the number of pump processes in a fully filled liquid condition is 1237 times the process, the product can last in conditions for 3 days 10 hours in standby conditions, and long battery charge is 4 hours 10 minutes.